Effect of Cowpea Sowing Dates on the Yield Performance of Maize and Cowpea Under Additive Intercropping System - Roy, Chandrika; Uddin, Md. Nesar; Ahmed, Md Targib; Nayan, Md.; Sadia, Halima Tujj; Rashid, Md. Harun (Fundamental and Applied Agriculture, 2025)
The experiment was conducted at the Agronomy Field Laboratory of the Department of Agronomy, Bangladesh Agricultural University, Mymensingh during the period from November 2023 to April 2024 to study the effect of sowing dates of cowpea on the productivity of maize-cowpea intercropping system. A local cowpea variety (V1) and Japanese cultivar (V2) was planted in a maize based intercropping system at different sowing dates. The experiment comprised two factors as-Factor A: (V1: Local cowpea variety, V2: Japanese cultivar); Factor B: (S1: Cowpea sown simultaneously with maize; S2: Cowpea sown 15 DAS of maize; S3: Cowpea sown 30 DAS of maize; S4: Cowpea sown 45 DAS of maize). The experiment was laid out in a randomized complete block design (RCBD) with three replications. The result of the study showed that the growth and yield of maize was not affected by cowpea varieties and different sowing dates. Between the cowpea varieties the V2 (Japanese variety) showed better performance in relation to growth and yield potential. On the other hand, among the sowing dates, the cowpea varieties planted simultaneously with maize gave the best yield (8.36 ± 0.61 t ha-1) compared to other treatments. Simultaneous sowing (S1) resulted in the tallest maize plants (200.67 cm) and the highest cowpea fresh pod yield (16.28 t ha-1), indicating efficient resource sharing. The V2 (Japanese cultivar) gave best result for number of pods per plant (14.66 ± 3.11), pod length (36.09 ± 4.22 cm), fresh pod yield (13.54 ± 4.15 t ha-1), stover yield (13.53 ± 4.15 t ha-1). The S1 treatment showed best result for number of pods per plant (16.48 ± 2.79), pod length (35.67 ± 6.94 cm), number of seeds per plant (16.57 ± 1.77), fresh pod yield (16.28 ± 2.55 t ha-1), stover yield (2.01 ± 0.12 t ha-1). In most of the cases the S4 treatment gave lowest result. These results indicated that cowpea variety and its various sowing time do not affect the yield and yield contributing characters of maize and the Japanese cowpea variety performed best when planted simultaneously with maize.